Attrition in Interpersonal Psychotherapy Among Women With Post-traumatic Stress Disorder Following Sexual Assault - Proença, Cecília R.; Markowitz, John C.; Prado, Euthymia A.; Braga, Rosaly; Coimbra, Bruno M.; Mello, Thays F.; Maciel, Mariana R.; Pupo, Mariana; Póvoa, Juliana; Mello, Andrea F.; Mello, Marcelo F. (Frontiers in Psychology, 2019)
Abstract: An estimated 16.9% of adult Brazilian women experience sexual assault in their lifetime. Almost half of women who suffer such trauma develop posttraumatic stress disorder (PTSD). Markowitz et al. (2015) found that an affect-focused non-exposure therapy, Interpersonal Psychotherapy (IPT), adapted to treat PTSD (IPT-PTSD) had similar efficacy to and lower dropout rates than Prolonged Exposure (PE), the “gold standard,” most studied exposure therapy for PTSD. Objective: To assess attrition rates in IPT of sexually assaulted women recently diagnosed with PTSD. Method: The current study derives from a two-arm, randomized controlled clinical trial of sexually assaulted women with PTSD who received 14 weeks of standardized treatment with either IPT-PTSD or sertraline. Sample: The thirty-two patients in the IPT treatment arm were analyzed. Result: Overall attrition was 29%. One patient was withdrawn because of suicidal risk; four dropped out pre-treatment, and five dropped out during IPT-PTSD. If the excluded patient is considered a dropout, the rate increases to 31%. Discussion: This is the first formal study of IPT for PTSD specifically due to sexual assault. IPT attrition approximated dropout rates in PE studies, which are often around 30%, and to the sertraline group in our study (34.5%). Further research should compare IPT and PE among sexually assaulted women to clarify our hypothesis that IPT could be an attractive alternative approach for this patient group.